What engineers know and How they know It. Analytical studies from aeronautical history, Walter G. Vincenti, Londres, The John Hopkins University Press, 1990, 326 páginas. - Lawler, Diego (1999)
Fil: Lawler, Diego. Universidad de Buenos Aires; Argentina.